Four Dimensions of Criticism Against Gender-Fair Language. - Vergoossen, Hellen Petronella; Renström, Emma Aurora; Lindqvist, Anna; Gustafsson Sendén, Marie (Sex Roles, 2020)
The gender-neutral third-person pronoun singular hen was recently introduced in Swedish as a complement to she (hon) and he (han). The initiative to add hen initially received strong criticism. In the present study, we analyzed 208 arguments from 168 participants with critical attitudes toward hen. We used Blaubergs' (1980) and Parks and Roberton's (1998) taxonomies of critical arguments against past gender-fair language reforms in English in the 1970s and 1990s as a basis for coding the arguments. A majority of arguments (80.7%) could be coded into existing categories, indicating that criticisms of gender-fair language initiatives are similar across different times and cultural contexts. Two categories of arguments did not fit existing categories (19.3%): gender-neutral pronouns are distracting in communication and gender information is important in communication. Furthermore, we established four overarching dimensions that capture assumptions and beliefs underlying gender-fair language criticism: (a) Defending the Linguistic Status Quo (39.4%), (b) Sexism and Cisgenderism (27.4%), (c) Diminishing the Issue and Its Proponents (26.9%), and (d) Distractor In Communication (6.3%). These dimensions of criticisms should be considered and addressed in different ways when implementing gender-fair language.